2006
DOI: 10.1038/nbt1215
|View full text |Cite
|
Sign up to set email alerts
|

A consensus epitope prediction approach identifies the breadth of murine TCD8+-cell responses to vaccinia virus

Abstract: The value of predictive algorithms for identifying CD8+ T (T(CD8+))-cell epitopes has not been adequately tested experimentally. Here we demonstrate that conventional bioinformatic methods predict the vast majority of T(CD8+)-cell epitopes derived from vaccinia virus WR strain (VACV-WR) in the H-2(b) mouse model. This approach reveals the breadth of T-cell responses to vaccinia, a widely studied murine viral infection model, and may provide a tool for developing comprehensive antigenic maps of any complex path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
484
3
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 508 publications
(502 citation statements)
references
References 14 publications
11
484
3
4
Order By: Relevance
“…Similar ranges of binding affinities were detected for VACV epitopes restricted by other human (12,13) and murine (7,8,11) class I MHC molecules. Also, a recent exhaustive study in the mouse H-2 b system revealed that in the course of VACV infection D b and K b molecules present 22 and 27 epitopes, respectively (11). Thus, the number of different VACV epitopes presented by a given MHC molecule seems to be in the same range in either the murine or human system.…”
Section: Discussionsupporting
confidence: 50%
“…Similar ranges of binding affinities were detected for VACV epitopes restricted by other human (12,13) and murine (7,8,11) class I MHC molecules. Also, a recent exhaustive study in the mouse H-2 b system revealed that in the course of VACV infection D b and K b molecules present 22 and 27 epitopes, respectively (11). Thus, the number of different VACV epitopes presented by a given MHC molecule seems to be in the same range in either the murine or human system.…”
Section: Discussionsupporting
confidence: 50%
“…The predictions were performed for 8–11‐mer peptides with NetMHC 4.0,18 NetMHC 3.4,19 NetMHCpan 3.0,20 NetMHCpan 2.8,20 NetMHCcons 1.1,21 Consensus,22 PickPocket 1.1,23 SMM,24 SMMPMBEC,25 BIMAS,26 and SYFPEITHI 27. Results of all prediction algorithms were combined.…”
Section: Methodsmentioning
confidence: 99%
“…For certain experimental systems, it may also be possible to use CD8 + T-cell-enriched cell populations from virus-immunized animals, since, during the acute phase of infection, virusspecific T cells may comprise at a large percentage of CD8 + T cells (Moutaftsi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%